Kajian Signage dan Elemen Wayfinding di Kampus Perguruan Tinggi (Studi Kasus : Kampus ITS Surabaya) - Vippy Dharmawan; Nanik Rachmaniyah (Universitas Sebelas Maret Surakarta, 2021)
A wide university campus which consist of many buildings need a good signage and wayfinding system arrangement. Meanwhile, the development of campus buildings is not necessarily accompanied by integrated wayfinding system planning. This article explain the finding of study on signage and wayfinding system on ITS Campus in Surabaya. The purpose of this study is to find out how signages and elements of the area work in wayfinding system on the campus. This qualitative descriptive study used direct observation in collecting data in the field. The result shows that generally the wayfinding system on the campus has been well implemented. However, it needs to optimize the signages that already available so that wayfinding activity can be carried out more easily by people who have not been familiar with the campus area